Quantitative Reasoning and Structural Complexity for Claim-Centric Argumentation - Fichte, Johannes K.; Hecher, Markus; Mahmood, Yasir; Meier, Arne (Proceedings of the Thirty-Second International Joint Conference on Artificial Intelligence)
Argumentation is a well-established formalism for nonmonotonic reasoning and a vibrant area of research in AI. Claim-augmented argumentation frameworks (CAFs) have been introduced to deploy a conclusion-oriented perspective. CAFs expand argumentation frameworks by an additional step which involves retaining claims for an accepted set of arguments. We introduce a novel concept of a justification status for claims, a quantitative measure of extensions supporting a particular claim. The well-studied problems of credulous and skeptical reasoning can then be seen as simply the two endpoints of the spectrum when considered as a justification level of a claim. Furthermore, we explore the parameterized complexity of various reasoning problems for CAFs, including the quantitative reasoning for claim assertions. We begin by presenting a suitable graph representation that includes arguments and their associated claims. Our analysis includes the parameter treewidth, and we present decomposition-guided reductions between reasoning problems in CAF and the validity problem for QBF.

Parameterized Complexity of Propositional Inclusion and Independence Logic - Mahmood, Yasir; Virtema, Jonni (Logic, Language, Information, and Computation)

Logics with probabilistic team semantics and the Boolean negation - Hannula, Miika; Hirvonen, Minna; Kontinen, Juha; Mahmood, Yasir; Meier, Arne; Virtema, Jonni (18th European Conference on Logics in Artificial Intelligence, JELIA 2023, Proceedings)
Keywords: dice enexa mahmood

Configuration and Evaluation - Hanselle, Jonas Manuel; Hüllermeier, Eyke; Mohr, Felix; Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Tornede, Alexander; Wever, Marcel Dominik (On-The-Fly Computing – Individualized IT-services in dynamic markets)
Keywords: dice ngonga sfb901 sherif

Lingua Franca - Entity-Aware Machine Translation Approach for Question Answering over Knowledge Graphs - Srivastava, Nikit; Perevalov, Aleksandr; Kuchelev, Denis; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille; Both, Andreas (Proceedings of the 12th Knowledge Capture Conference 2023, K-CAP 2023, Pensacola, FL, USA, December 5-7, 2023)
Keywords: dice kuchelev moussallem ngonga srivastava

Learning Permutation-Invariant Embeddings for Description Logic Concepts - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Advances in Intelligent Data Analysis XXI: 21st International Symposium on Intelligent Data Analysis, IDA 2023, Louvain-la-Neuve, Belgium, April 12–14, 2023, Proceedings)
Keywords: 318 SFB-TRR demir dice enexa ngonga sail

COBALT: A Content-Based Similarity Approach for Link Discovery over Geospatial Knowledge Graphs - Becker, Alexander; Ahmed, Abdullah Fathi Ahmed; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (SEMANTiCS)
Keywords: ahmed becker dice ngonga sail sherif

Method Engineering – a Systematic Literature Review on Scopus Base - Wilke, Daria; Grewe, Carolin; Thavathilakarjah, Dhusjanth; Anacker, Harald; Dumitrescu, Roman

Method to support the selection of localization technologies for Industry 4.0 - Seidenberg, Tobias; Ayoub, Joe; Figge, Mike; Anacker, Harald; Dumitrescu, Roman

Sustainability Data Map: Framework for Data-Based Product Carbon Footprinting of Technical Products - Schreiner, Nick; Kürpick, Christian; Kühn, Arno; Dumitrescu, Roman

PEA: core-analogue for non-cohesive games - Aslan, Fatma; Duman, Papatya; Trockel, Walter (Economics Bulletin)

Transferkonzept eines Kompetenzzentrums der Arbeitsforschung in einer von mittelständischen Unternehmen geprägten Region - Gabriel, Stefan; Fechtelpeter,, Christian; Wulf, Jessica; Leßmann, Salome; Dumitrescu, Roman

A World Full of Privacy and Security (Mis)conceptions? Findings of a Representative Survey in 12 Countries - Herbert, Franziska; Becker, Steffen; Schaewitz, Leonie; Hielscher, Jonas; Kowalewski, Marvin; Sasse, M. Angela; Acar, Yasemin; Dürmuth, Markus (Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems, CHI 2023, Hamburg, Germany, April 23-28, 2023)

"Always Contribute Back": A Qualitative Study on Security Challenges of the Open Source Supply Chain - Wermke, Dominik; Klemmer, Jan H.; Wöhler, Noah; Schmüser, Juliane; Sri Ramulu, Harshini; Acar, Yasemin; Fahl, Sascha (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

Pushed by Accident: A Mixed-Methods Study on Strategies of Handling Secret Information in Source Code Repositories - Krause, Alexander; Klemmer, Jan H.; Huaman, Nicolas; Wermke, Dominik; Acar, Yasemin; Fahl, Sascha (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023)

It’s like flossing your teeth: On the Importance and Challenges of Reproducible Builds for Software Supply Chain Security - Fourné, Marcel; Wermke, Dominik; Enck, William; Fahl, Sascha; Acar, Yasemin (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

"In Eighty Percent of the Cases, I Select the Password for Them": Security and Privacy Challenges, Advice, and Opportunities at Cybercafes in Kenya - Munyendo, Collins W.; Acar, Yasemin; Aviv, Adam J. (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

"We are a startup to the core": A qualitative interview study on the security and privacy development practices in Turkish software startups - Keküllüoglu, Dilara; Acar, Yasemin (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

Ethical Frameworks and Computer Security Trolley Problems: Foundations for Conversations - Kohno, Tadayoshi; Acar, Yasemin; Loh, Wulf (CoRR)

"Would You Give the Same Priority to the Bank and a Game? I Do Not!" Exploring Credential Management Strategies and Obstacles during Password Manager Setup - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Acar, Yasemin; Fahl, Sascha (Nineteenth Symposium on Usable Privacy and Security, SOUPS 2023, Anaheim, CA, USA, August 5-7, 2023)